A receptor-binding domain-based nanoparticle vaccine elicits durable neutralizing antibody responses against SARS-CoV-2 and variants of concern. Issue 1 (31st December 2023) - Lee, I-Jung; Lan, Yu-Hua; Wu, Ping-Yi; Wu, Yan-Wei; Chen, Yu-Hung; Tseng, Sheng-Che; Kuo, Tzu-Jiun; Sun, Cheng-Pu; Jan, Jia-Tsrong; Ma, Hsiu-Hua; Liao, Chun-Che; Liang, Jian-Jong; et al.
ABSTRACT: Numerous vaccines have been developed to address the current COVID-19 pandemic, but safety, cross-neutralizing efficacy, and long-term protectivity of currently approved vaccines are still important issues. In this study, we developed a subunit vaccine, ASD254, by using a nanoparticle vaccine platform to encapsulate the SARS-CoV-2 spike receptor-binding domain (RBD) protein. As compared with the aluminum-adjuvant RBD vaccine, ASD254 induced higher titers of RBD-specific antibodies and generated 10- to 30-fold more neutralizing antibodies. Mice vaccinated with ASD254 showed protective immune responses against SARS-CoV-2 challenge, with undetectable infectious viral loads and reduced typical lesions in lung. Besides, neutralizing antibodies in vaccinated mice lasted for at least one year and were effective against various SARS-CoV-2 variants of concern, including B.1.1.7 (Alpha), B.1.351 (Beta), P.1 (Gamma), B.1.617.2 (Delta), and B.1.1.529 (Omicron). Furthermore, particle size, polydispersity index, and zeta-potential of ASD254 remained stable after 8-month storage at 4°C. Thus, ASD254 is a promising nanoparticle vaccine with good immunogenicity and stability to be developed as an effective vaccine option in controlling upcoming waves of COVID-19.